2001
DOI: 10.1161/01.cir.103.21.2617
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria as Targets for Nitric Oxide–Induced Protection During Simulated Ischemia and Reoxygenation in Isolated Neonatal Cardiomyocytes

Abstract: Pretreatment with an NO donor induces a modest, sustained mitochondrial depolarization and protects cardiomyocytes from sI/R injury. The demonstrated reduction in mitochondrial Ca(2+) uptake possibly reduces cytosolic Ca(2+) overload, providing a likely mechanism for NO-induced protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 33 publications
2
80
1
Order By: Relevance
“…This competition transiently inhibits oxidative phosphorylation, precluding maintenance of ⌬⌿ m in the face of ongoing ATP synthesis. By dissipating ⌬⌿ m during elevations of [Ca 2ϩ ] cytosol , NO may reduce mitochondrial Ca 2ϩ uptake and subsequent cell death in neurons, a phenomenon reported in cardiomyocytes in vitro during ischemia-reperfusion injury (Rakhit et al, 2001). Because NMDA induces mild ⌬⌿ m dissipation in newborn hippocampal neurons with little subsequent death, we hypothesized that this ⌬⌿ m dissipation results from NMDA-induced NO production and that this NO production protects neurons after NMDA.…”
Section: Introductionmentioning
confidence: 93%
“…This competition transiently inhibits oxidative phosphorylation, precluding maintenance of ⌬⌿ m in the face of ongoing ATP synthesis. By dissipating ⌬⌿ m during elevations of [Ca 2ϩ ] cytosol , NO may reduce mitochondrial Ca 2ϩ uptake and subsequent cell death in neurons, a phenomenon reported in cardiomyocytes in vitro during ischemia-reperfusion injury (Rakhit et al, 2001). Because NMDA induces mild ⌬⌿ m dissipation in newborn hippocampal neurons with little subsequent death, we hypothesized that this ⌬⌿ m dissipation results from NMDA-induced NO production and that this NO production protects neurons after NMDA.…”
Section: Introductionmentioning
confidence: 93%
“…32 NO is known to abolish mitochondrial oxidant damage and calcium overload, and reduce superoxide anion production via an efficient suppression on the activity of NAD(P)H oxidase and the assembly of NAD(P)H oxidase subunits. 1,33 Maintenance of NO levels is critical for recovery of heart failure after ischemic injury. As part of a self-protective process, we found that CHF causes a modest increase in interstitial NO levels (consistent with a previous publication 34 ) and may be derived from activated NOS isoforms and/or a NOS-independent pathway.…”
Section: Cardioprotection By Kallistatin Via Antioxidation L Gao Et Almentioning
confidence: 99%
“…An additional limitation is that NO formation from NO synthase requires oxygen as substrate, a molecule whose availability becomes limited during ischemia. We therefore considered the use of nitrite in this context for the following reasons: (a) it is a naturally occurring substance with no potentially toxic "leaving group"; (b) it is selectively reduced to NO in tissues with low oxygen tension and low pH (4, 6-13, 34, 35); and (c) NO is known to maintain heme proteins in a reduced and liganded state (36)(37)(38), to limit free iron-and heme-mediated oxidative chemistry (39)(40)(41), to transiently inhibit cytochrome c oxidase and mitochondrial respiration (42)(43)(44)(45), and to modulate apoptotic effectors (46), all mechanisms that might participate in cytotoxicity after severe ischemia.…”
Section: Introductionmentioning
confidence: 99%